Bentuk Pemertahanan Bahasa Oleh Mahasiswa Penutur Bahasa Jawa Dialek Mataraman di Malang: Kajian Pemertahanan Bahasa - prisma Satya Wicaksana; Pandu Meidian Pratama (IKIP Budi Utomo Malang, 2020)
Javanesse language is one most the largest speakers in Indonesia, this language must survive in all times and from many foreign languages. This research is focus on maintaining the language used by the students who speaks mataraman dialect in Malang. In this study use the sociolinguistic theory. The purpose of this research is describing the maintaining language, especially on mataraman dialects, describing a word category in linguistic pattern use by students with the mataraman dialects in Malang. This research use descriptive qualitative approach. Technique in this research used in data retrieval in this study was carried out by searching for the student community from same areas, especially from mataraman area; using a recording technic while collected the data; transcription data; translate data into Indonesian language using a Javanesse-Indonesia dictionary. While the data is already collected, the next step is analyze the data and groupped the data into classes of word from Javanesse language. Results from this research is students with mataraman dialects in Malang is able to using a language patterns in Javanesse language, and able to maintaining the languages in arek dialects community with good criteria.